# Answer to Question #16745 in Algebra for Blessy Lorenz

Question #16745

3x^2 + 6x - 9 =

Expert's answer

3x^2 + 6x - 9 =3(x^2 + 2x - 3)

x^2 + 2x - 3=0

x1,2=(-2+-sqrt(4+12))/2=(-2+-4)/2=-1+-2

x1=-1+2=1

x2=-1-2=-3

Therefore x^2 + 2x - 3=(x-1)(x+3) and hence 3x^2 + 6x - 9 =3(x^2 + 2x - 3)=

x^2 + 2x - 3=0

x1,2=(-2+-sqrt(4+12))/2=(-2+-4)/2=-1+-2

x1=-1+2=1

x2=-1-2=-3

Therefore x^2 + 2x - 3=(x-1)(x+3) and hence 3x^2 + 6x - 9 =3(x^2 + 2x - 3)=

**3(x-1)(x+3)**
## Comments

## Leave a comment